Perlindungan Hukum Dokter Program Pendidikan Dokter Spesialis (PPDS) Terhadap Pelimpahan Wewenang Dokter Spesialis dalam Pelayanan Medis di Rumah Sakit (Studi Kasus di Rumah Sakit Umum Pusat Dr. M. Djamil Padang Bagian Obstetri dan Ginekologi) - Nadia Tiara Syahredi Adnani; Syofirman Syofyan; Yussy Adelina Mannas (UNES Law Review, 2023)
The doctor's service at a hospital, becomes the future cycle of the hospital itself in the middle of society. The impact of a service and the acceleration of services performed by doctors and other medical personnel will have an impact, both positive and negative, on the image of the hospital. Legal questions that may arise from the hospital service when the medical action that should be performed by the doctor responsible for the patient but carried out by the general practitioner. Medical action carried out by a caregiver against a patient will be a legal issue for doctors and hospitals when such action is detrimental to the patient, while such an action is a fulfilment of the duty that should be performed by the Patient Responsible Doctor.